The Integration of Self-Efficacy, Teachers’ Instructional Skills, and Learning Motivation in Shaping Students’ Creative Thinking Ability”: Integrasi Efikasi Diri, Keterampilan Mengajar Guru, dan Motivasi Belajar dalam Pembentukan Kemampuan Berpikir Kreatif Siswa - Nur, Anisa Oktavia; Murniawaty, Indri (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Students’ creative thinking ability in economics learning remains relatively low, despite its importance in developing higher-order thinking skills in 21st-century education. Specific Background: Previous studies have predominantly examined self-efficacy, teacher instructional skills, and learning motivation separately, limiting a comprehensive understanding of their combined role in shaping creativity. Knowledge Gap: There is limited empirical evidence integrating personal, environmental, and behavioral factors within a unified analytical framework based on Social Cognitive Theory. Aims: This study aims to analyze the role of self-efficacy, teachers’ instructional skills, and learning motivation in shaping students’ creative thinking ability. Results: Using a quantitative causality design with 63 students, the findings reveal that self-efficacy and teacher instructional skills show significant relationships with creative thinking ability (p < 0.05), while learning motivation does not demonstrate a significant partial relationship; however, all variables jointly show a significant contribution. Novelty: The study offers an integrated analytical model combining psychological and pedagogical factors to explain students’ creative thinking ability within economics learning. Implications: The findings highlight that developing creative thinking requires not only motivational aspects but also the reinforcement of self-efficacy and the improvement of teacher instructional practices, supporting a more holistic and integrated learning approach. Highlights• Integration of psychological and pedagogical variables explains student creativity patterns• Instructional competence shows measurable contribution to idea generation processes• Joint variable interaction provides stronger explanatory model than single-factor analysis KeywordsSelf Efficacy; Teacher Instructional Skills; Learning Motivation; Creative Thinking Ability; Economics Learning